Developing a Web-Based Vocabulary Size Test for Indonesian EFL Learners - Ignatius Tri Endarto; Adaninggar Septi Subekti (Universitas Teknokrat Indonesia, 2020)
One important aspect of English language learning is vocabulary. However, the availability of vocabulary proficiency tests, both manual and computer-based, is still limited. Almost all currently existing vocabulary tests are monolingual and have not accommodated the needs of EFL learners. The objective of this study was to develop a web-based vocabulary size test for English learners in Indonesia. It consisted of 6 stages, namely: (1) needs analysis; (2) corpus selection and corpus data analysis; (3) sampling to select words from corpus data; (4) generating test items; (5) developing a web-based version of the test and pilot study; and (6) reflection and evaluation. Pilot study involved having a sample group of English learners in Indonesia try out the designed vocabulary size test. A paired-samples t-test was then used to determine whether there was a significant difference between the learners’ scores on the designed test and those on a free online vocabulary size test not specifically designed for Indonesian test takers. The t-test indicated that there was a significant difference between the designed test scores (M=6433, SD=1169) and free online test scores (M=5700, SD=1616); t(35)=-3.597, p = 0.001. The identifiable factors which seemed to contribute to this difference were different corpus data (COCA vs. BNC), different varieties of English (American vs. British), and different formats (bilingual vs. monolingual). Despite the difference, there was a positive correlation between the two tests (Correlation = 0.657) meaning that higher scores on one of the tests equals higher scores on the other.